2013
DOI: 10.5194/bg-10-6141-2013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil carbon stocks in Brazil due to land use: paired site comparisons and a regional pasture soil survey

Abstract: Abstract. In this paper we calculated soil carbon stocks in Brazil studying 17 paired sites where soil stocks were determined in native vegetation, pastures and crop-livestock systems (CPS), and in other regional samplings encompassing more than 100 pasture soils, from 6.58 to 31.53 • S, involving three major Brazilian biomes: Cerrado, Atlantic Forest, and the Pampa. The average native vegetation soil carbon stocks at 10, 30 and 60 cm soil depth were equal to approximately 29, 64, and 92 Mg ha −1 , respectivel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
74
0
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 48 publications
15
74
0
16
Order By: Relevance
“…A full description of the study area can be found in Assad et al (2013). Briefly, we conducted two types of surveys: one at the regional level, exclusively in pasture soils, and another in which 17 plot-level paired sites were sampled encompassing soils of pastures, CPSs and native vegetation.…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…A full description of the study area can be found in Assad et al (2013). Briefly, we conducted two types of surveys: one at the regional level, exclusively in pasture soils, and another in which 17 plot-level paired sites were sampled encompassing soils of pastures, CPSs and native vegetation.…”
Section: Study Areamentioning
confidence: 99%
“…A bias in this scheme is that sampling sites were not randomly selected. A second bias is that, although all pastures were in use at the time they were sampled, it was difficult to visually assess their grazing conditions or stocking rates, which may affect the soil nutrient stocks (Maia et al, 2009;Braz et al, 2012;Assad et al, 2013). Paired sites were selected by the EMBRAPA (Empresa Brasileira de Pesquisa Agropecuária) regional offices and sampled between November and December 2011.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations